PENGARUH POLA MAKAN TERHADAP SISTEM IMUN PASIEN YANG MENGALAMI DIARE DI PUSKESMAS MOGANG - Pandiangan, Vany Natalia; Tamba, Lisna P.J.; Pulungan, Ahmad Shafwan S. (Jurnal Sains Indonesia, 2025)
Diarrhoeal disease is a condition in which the shape of faeces changes and the frequency of bowel movements increases abnormally. The emergence of the incidence of diarrhoea is the factor of providing an unhealthy diet is likely to cause diarrhoea so that it is more susceptible to disease. This study aims to analyse the relationship between diet and immune system of patients with diarrhoea in Mogang Health Centre. The results showed that diarrhoeal disease is a significant health problem in Indonesia, especially in toddlers, who have a high risk of dehydration and malnutrition. An unbalanced diet and lack of nutritional intake can contribute to a decrease in the immune system, thus helping the condition of diarrhoea sufferers. This study shows that children who consume a nutritionally balanced diet have a better immune system compared to those who rely on unhealthy foods.